Insulin and C-peptid responses to oral glucose tolerance test in patients with idiopathic hepatosteatosis - Muhsin KAYA,; Ali Reşit BEYLER,; Murat Faik ERDOĞAN, (Turkish Journal of Gastroenterology, 2019)
-